2014
DOI: 10.1007/s12311-014-0573-4
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and GABA-Metabolizing Enzymes in Post-mortem Cerebellum in Alzheimer’s Disease: Phosphate-Activated Glutaminase and Glutamic Acid Decarboxylase

Abstract: Enzymes of glutamate and GABA metabolism in postmortem cerebellum from patients with Alzheimer's disease (AD) have not been comprehensively studied. The present work reports results of original comparative study on levels of phosphate-activated glutaminase (PAG) and glutamic acid decarboxylase isoenzymes (GAD65/67) in autopsied cerebellum samples from AD patients and matched controls (13 cases in each group) as well as summarizes published evidence for altered levels of PAG and GAD65/67 in AD brain. Altered (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 60 publications
0
12
0
2
Order By: Relevance
“…Glutaminase dysregulation has been implicated in various neurodegenerative and neuroinflammatory diseases such as HIV-1 associated dementia, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer's disease (Burbaeva et al, 2014; D'Alessandro et al, 2011; Huang et al, 2011; Werner et al, 2001; Zhao et al, 2012), as well as neuropsychiatric diseases such as schizophrenia (Gluck et al, 2002). Our model is useful in that it provides a novel tool to assess the consequences of excess production of glutamate on brain function and the model may be used to test novel therapeutic strategies to alleviate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutaminase dysregulation has been implicated in various neurodegenerative and neuroinflammatory diseases such as HIV-1 associated dementia, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer's disease (Burbaeva et al, 2014; D'Alessandro et al, 2011; Huang et al, 2011; Werner et al, 2001; Zhao et al, 2012), as well as neuropsychiatric diseases such as schizophrenia (Gluck et al, 2002). Our model is useful in that it provides a novel tool to assess the consequences of excess production of glutamate on brain function and the model may be used to test novel therapeutic strategies to alleviate excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glutamianse is associated with various neurodegenerative and neuroinflammatory disesases such as HIV-1 associated dementia, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer's disease (Burbaeva et al, 2014; D'Alessandro et al, 2011; Huang et al, 2011; Werner et al, 2001; Zhao et al, 2012), as well as neuropsychiatric diseases such as schizophrenia (Gluck et al, 2002). Most recently, we demonstrated that glutaminase-containing extracellular vesicles from HIV-infected macrophages, air polutants-treated macrophages, and immune-activated microglia were neurotoxic (Liu et al, 2015; Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…по сравнению с контролем [20,21]. Следовательно, сни-жение уровня мозговой изоформы КФК, наблюдаемое в мозге пациентов с этими заболеваниями, является харак-терной особенностью этих расстройств, а не результатом терапии нейролептиками.…”
Section: рис 3 количество иммунореактивной кфк вв у больных шз (темunclassified
“…Thanks to the opposing functions, glutamate is excitatory while GABA is inhibitory, they play an important role in the central nervous system [1]. The disruption of the homeostasis of glutamate and GABA is not only connected to the neurological and psychiatric disorders such Alzheimer's disease [2], schizophrenia [3] and epi-lepsy [4], but it is also the result of exposure to some toxic substances: methoxychlor [5], 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) [6] and polychlorinated biphenyls (PCBs) [7]. Moreover, in the case of occupational exposure to toxic substances such as organic solvents (e.g., toluene) [8] and some metals (e.g., manganese), abnormalities in the levels of neurotransmitters were observed [9].…”
Section: Introductionmentioning
confidence: 99%